Field report contributed by Russell P. Baldner and Cathryn A. Baldner, summer 1982 - Baldner, Russell P.et al; Baldner, Cathryn A.et al (1982)
Field report was contributed by Russell P. Baldner and Carthryn A. Baldner. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1982. Epson - sheet feed